Analisis Yuridis Atas Kasus-Kasus Perbuatan Melawan Hukum Bidan Di Masyarakat - T. Keizerina Devi Azwar; Chastry Meher; Marice Simarmata; Hilbertus Sumplisius M. Wau (Talenta Publisher, Universitas Sumatera Utara, 2023)
This study aims to find out and analyze the responsibility of a midwife for unlawful acts that occur and are carried out in the midst of society. The profession of a midwife must provide health services including maternal health, child health, women's reproductive health and family planning based on responsible, accountable and competent services. However, in practice there are always individuals who commit violations and negligence that are against the law in society. The issues raised from this study are how to regulate unlawful acts by midwives and the extent of midwives' responsibility for PMH carried out in the community. The research method used is normative juridical research which is descriptive analytical using literature and case techniques supported by secondary data. Data analysis was carried out using qualitative research methods. The results of this study indicate that the regulation of unlawful acts by midwives can be found in Articles 1365, 1366, 1367 of the Civil Code, up to Article 58 of Law Number 36 of 2009 concerning Health. The midwife's responsibility for unlawful acts committed in the midst of the community is given as long as it is proven to have committed a violation and caused the patient to suffer losses due to negligence from the medical action given by the midwife, so that the midwife will be fully responsible such as imposing administrative sanctions starting from written warning sanctions to revoking the license to practice . Furthermore, the imposition of civil sanctions, namely giving compensation to patients, to imposing criminal sanctions due to negligence which resulted in the patient being seriously injured causing death. This study concludes that the imposition of sanctions and reprimands on midwives is given on the basis of the magnitude of the errors and omissions they have made so that the consequences will be midwifery administrative responsibility, civil liability based on unlawful acts, and criminal liability if proven to have committed gross negligence which resulted in the patient being seriously injured up to death. From this study it can be seen that a midwife must and should prioritize a midwife's professional attitude such as the public's expectations of a midwife's profile, for this reason the community expects and wants a midwife to continue to prioritize a friendly, skilled and responsive attitude in their field according to their expertise and competence.